2012
DOI: 10.1182/blood-2011-06-362582
|View full text |Cite
|
Sign up to set email alerts
|

TLR3 essentially promotes protective class I–restricted memory CD8+ T-cell responses to Aspergillus fumigatus in hematopoietic transplanted patients

Abstract: Aspergillus fumigatus is a model fungal pathogen and a common cause of severe infections and diseases. CD8 ؉ T cells are present in the human and murine T-cell repertoire to the fungus. However, CD8 ؉ T-cell function in infection and the molecular mechanisms that control their priming and differentiation into effector and memory cells in vivo remain elusive. In the present study, we report that both CD4 ؉ and CD8 ؉ T cells mediate protective memory responses to the fungus contingent on the nature of the fungal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
125
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 119 publications
(127 citation statements)
references
References 52 publications
(89 reference statements)
1
125
0
1
Order By: Relevance
“…Murine studies have shown that both CD8 + and CD4 + T cells mediate memory responses to fungi via the production of effector cytokines, such as IFN-γ, and, in the case of CD8 + T cells, through cytotoxic activity against fungus-laden cells (7)(8)(9)(10)(11). The requirement for IFN-γ in vaccine-mediated resistance was confirmed by vaccination of Ifng -/-or Il17ra -/-mice with Aspergillus conidia or Pep1p.…”
Section: Cd8 + T Cell Vaccination Against a Fumigatus Is Defective Imentioning
confidence: 81%
See 1 more Smart Citation
“…Murine studies have shown that both CD8 + and CD4 + T cells mediate memory responses to fungi via the production of effector cytokines, such as IFN-γ, and, in the case of CD8 + T cells, through cytotoxic activity against fungus-laden cells (7)(8)(9)(10)(11). The requirement for IFN-γ in vaccine-mediated resistance was confirmed by vaccination of Ifng -/-or Il17ra -/-mice with Aspergillus conidia or Pep1p.…”
Section: Cd8 + T Cell Vaccination Against a Fumigatus Is Defective Imentioning
confidence: 81%
“…Despite the lack of evidence for susceptibility to aspergillosis in patients with congenital absence of T cells (2), CD4 + and CD8 + T cells are present in the human T cell repertoire to the fungus (3)(4)(5), and adoptive transfer of A. fumigatus-specific CD4 + T cells conferred protection against invasive aspergillosis (5,6). As with other fungi (7-10), antigen-specific CD4 + and CD8 + T cell memory to A. fumigatus has been demonstrated in experimental aspergillosis (11). However, the molecular mechanisms leading to T cell memory are largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…96 After BM transplantation, T cell proliferative responses to specific antigens, such as candidin, tetanus toxoid, tuberculin or toxoplasma, are absent in about 20-50% of patients, even up to a year after transplantation. 20 Primary T cell immunity against fungi is provided by CD4C Th1 and Th17 cells [158][159][160][161] as well as memory CD8C T-cell cells. 160 Consequently, at 3 months or later after HSCT, fewer than a quarter of patients will have detectable functional T cell responses against the most common invasive fungal infection.…”
Section: Functional Reconstitution Of T Cellsmentioning
confidence: 99%
“…Less well appreciated is the influence of CD8 + T cells on the host response. Antigen-reactive CD8 + T cells can be elicited by Aspergillus antigens, and protection relies on recognition of fungal RNA by TLR3 (11,12). That T cells exert a strong influence on the host response has major implications not only for the immunopathogenesis but also for the design of prophylactic or therapeutic vaccines for this pathogen.…”
Section: Cellular Immunity To Aspergillusmentioning
confidence: 99%
“…While blockade of PD-1 enhances HIV- and SIV-specific T cell cytokine production and proliferation in vitro (9, 10), initially there was skepticism that this method would restore immunological function in the pathogenic RM SIV model in vivo (12). This skepticism was based on the premise that if in vivo blockade of the PD-1 inhibitory receptor in chronic SIV infection could result in enhanced antiviral T and B cell responses, it could also potentially exacerbate bystander T cell activation in an already persistent inflammatory setting, potentially leading to accelerated disease progression.…”
Section: Can Preventing Exhaustion Improve Immune Responses?mentioning
confidence: 99%